The Archetypal Images in â€œCoralineâ€ Novel By Neil Gaiman (2002) - Glorya Samosir; Gaguk Rudianto (Institut Agama Islam Negeri Palopo, 2023)
The dark fantasy children's book Coraline by Neil Gaiman described Coraline's adventured as she tried to uncover strange and frightening secrets in her new home. The goal of this study was to describe the archetypal images that emerged in the Coraline novel based on Carl Jung's theory of the archetypal image. The issue identified in this study is that many readers are still not aware of what an archetypal description in a novel implies. This research was a qualitative descriptive research proposed by Creswell (2018). In collecting data, researchers used observation (reading) and note-taking techniques. Then, for data analysis methods, the researchers used content analysis and interpretation techniques. The result of this research was the discovery of 15 data of archetypal images in the novel Coraline. The 15 data consisted of four data of terrible mother, two data of demon lover, two data of black color, two data of tree, one data of red color, one data of rising sun, one data of desert, one data of serpent, and one data of circle. Considering the findings of the study, it could be concluded that the novel Coraline used a number of image archetypes to convey hidden meanings through the use of symbols.